Literature Review: The Relationship Between Benson Relaxation Technique and Blood Pressure Reduction in Elderly Patients with Hypertension - Munariyah, Indah; Nurdiana, Ilvi; Sofia Indriani, Riska; Suwanti (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Hypertension is a major global health problem contributing to high morbidity and mortality due to cardiovascular complications. Non-pharmacological therapies, such as the Benson relaxation technique, are increasingly used as complementary approaches to control blood pressure. This study employed a descriptive literature review design. Articles were systematically searched through Google Scholar and Garuda databases within the publication period of 2021–2025. Inclusion criteria included original research articles, full-text availability, and relevance to the topic of Benson relaxation and blood pressure reduction. A total of five eligible articles were selected and analyzed narratively. All reviewed studies demonstrated a significant reduction in both systolic and diastolic blood pressure following the implementation of the Benson relaxation technique (p < 0.05). The intervention was typically conducted for 5–10 minutes, with a frequency of 1–2 times per day over 5–7 days. The findings indicate that Benson relaxation effectively promotes physiological relaxation by reducing sympathetic nervous system activity and enhancing parasympathetic response, leading to blood pressure stabilization. Conclusion of this study was the Benson relaxation technique is an effective non-pharmacological intervention for reducing blood pressure in patients with hypertension. It can be recommended as a complementary nursing intervention to improve patient outcomes.